Desempenho de cultivares de cebola em função do espaçamento entre plantas - Santos, Jandeilson Pereira dos (2017)
In Brazil, The onion is traditionally cultivated by the transplant system of seedlings, However, the system of direct sowing comes been adopted by the producers of Minas Gerais, São Paulo and Goiás. In the Northeast region, in addition to Bahia, many producers uses this method of sowing, together with hybrid cultivars in dense planting and drip irrigation, However the responses regarding productivity and bulb quality are not always as expected. The objective of this work was to evaluate the performance of onion cultivars in function of the spacing between plants. The experimental design was in randomized complete block in a 3 x 4 factorial scheme, with four replications. The treatments consisted of three onion cultivars (Vale Ouro IPA 11, Serena and Rio das Antas) and four plant spacings (3, 6, 8 and 10 cm). The evaluated characteristics were: plant height, number of leaves, percentages of bulbs classes 1, 2, 3 and 4, total, commercial and non-commercial productivity of bulbs, average bulb mass, bulb mass weight, Bulb format, soluble solids, titratable acidity, soluble solids ratio / titratable acidity. The cultivars Rio das Antas and Serena obtained higher productive performance, being the most suitable for cultivated crops. The IPA 11 cultivar, regardless of the spacing between plants, provided higher pungency and soluble solids content, being the most suitable for industrial processing and preserves